Characterization and Antibacterial Activity of a Polysaccharide Produced From Sugarcane Molasses by Chaetomium globosum CGMCC 6882 - Ma, Li; Guo, Xueliang; Yang, Jiaoyang; Zeng, Xiangru; Ma, Kaili; Wang, Lu; Sun, Qi; Wang, Zichao (Frontiers in Nutrition, 2022)
As a by-product from sugar industry containing many sugars, proteins, nitrogenous materials and heavy metals, molasses is rarely used for polysaccharide production. In present work, a Chaetomium globosum CGMCC 6882 polysaccharide (CGP-SM) was successfully produced from sugarcane molasses. The yield of CGP-SM was 5.83 ± 0.09 g/L and its protein content was 2.41 ± 0.12% (w/w). Structural analysis showed that CGP-SM was a crystalline and amorphous polysaccharide contained rhamnose, glucosamine, galactose, glucose, mannose, fructose and glucuronic acid in the molar ratio of 10.31: 1.14: 2.07: 59.55: 42.65: 1.92: 9.63. Meanwhile, weight-average molecular weight (Mw), number-average molecular weight (Mn) and polydispersity (Mw / Mn) of CGP-SM were 28.37 KDa, 23.66 KDa and 1.199, respectively. Furthermore, bacteriostatic assay indicated that CGP-SM inhibited the growth of Escherichia coli and Staphylococcus aureus in a concentration-dependent manner, and its inhibitory effect on S. aureus was higher than that of E. coli. Above all, this work provides a green method for production of bioactive polysaccharide from sugarcane molasses.